Rise up and sing! : power, protest, and activism in music - Warner, Andrea (Greystone Kids/Greystone Books, 2023)
"In Rise Up and Sing!, Andrea Warner explores how music has contributed to the fight for social justice. Across eight areas of activism--the climate emergency, Indigenous rights, civil rights, disability rights, 2SLGBTQIA+ rights, gender equality, the peace/anti-war movement, and human rights--Warner introduces some of the artists, past and present, who have made a difference both on stage and off. Through ground-breaking artists and iconic moments, Rise Up and Sing! shows us that a song is never just a song, and that music really does have the power to change the world" --